Analisis Pengaruh Teknologi terhadap Pertumbuhan Ekonomi di Kota Medan Tahun 2020-2023 - Amri Yahya; Haidir Ali; Muhammad Arif Pohan (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This study aims to analyze the effect of technological development on economic growth in Medan City in the period 2020-2023. By using multiple linear regression analysis method, this study examines the relationship between independent variables such as technology investment, technology infrastructure, and human resources in technology with the dependent variable which is Gross Regional Domestic Product (GRDP) of Medan City. The results show that technology investment and human resources in technology have a positive and significant influence on the economic growth of Medan City, while technology infrastructure has no significant influence. These findings highlight the importance of increasing investment and human resource development in technology to boost economic growth in Medan City.